Analisis Jenis dan Bentuk Onomatope dalam Anime Saiki Kusou no Psi-Nan - Yanuar Lutfi Rohman (Universitas Diponegoro, 2025)
This research aims to provide deeper insights into the role of onomatopoeia in anime and its application in Japanese language learning. This study analyzes the types, forms, and meanings of onomatopoeia in the second season of the anime Saiki Kusuo no Psi-nan. Onomatopoeia are linguistic elements that imitate sounds or describe certain states and play an important role in japanese language, especially in media such as anime. This study employs a qualitative descriptive method to identify and classify onomatopoeia into four categories: giongo (sound effects), giseigo (human sounds), gitaigo (descriptive expressions), and gijougo (emotional expressions). Analyzing all 24 episodes of the second season, the study found 400 instances of onomatopoeia, each contributing to the depiction of atmosphere, character expression, and comedic elements in the anime. The findings reveal that onomatopoeia is as expressive tool in visual and auditory communication. <a href=